Pengaruh Beban Kerja dan Pendidikan Pelatihan Terhadap Kinerja Petugas Imunisasi: (Studi pada Puskesmas Di Wilayah Kerja Dinas Kesehatan Kota Banjar) - Imas Masruroh Fuad Diyah; Ading Rahman Sukmara (Pajak dan Manajemen Keuangan, 2024)
The problems faced in this study include (1) How does the workload affect the performance of immunization officers at the Health Center in the Working Area of the Banjar City Health Office? (2) What is the effect of training education on the performance of immunization officers at the Health Center in the Working Area of the Banjar City Health Office? (3) How does workload and training education affect the performance of immunization officers at the Health Center in the Working Area of the Banjar City Health Office? This study aims to study, know, and analyze (1) The effect of workload on the performance of immunization officers at health centers in the working area of the Banjar City Health Office. (2) The effect of education and training on the performance of immunization officers at the Health Center in the Working Area of the Banjar City Health Office. (3) The effect of workload and training education on the performance of immunization officers at the Health Center in the Working Area of the Banjar City Health Office. The method used in this study is an explanatory survey, while the data analysis technique is validity test, reliability test, descriptive statistics, Inductive Statistical Analysis with Multiple Regression. The results of the study inform that (1) The workload at the Health Center in the work area of the Banjar City Health Office is very high. With the highest score on the physical demand indicator and the lowest score on the task demand indicator. The workload has a positive effect on the performance of immunization officers at the Health Center in the work area of the Banjar City Health Office. This means that if the workload is increased, the performance of immunization officers at the Health Center in the work area of the Banjar City Health Office will also increase. (2) Training education at Puskesmas in the work area of the Banjar City Health Office is very high. With the highest score on the behavior indicator and the lowest value on the reaction indicator. Training education has a positive effect on the performance of immunization officers at health centers in the work area of the Banjar City Health Office. This means that if training education is improved, the performance of immunization officers at health centers in the work area of the Banjar City Health Office will also increase. (3) The performance of immunization officers at the Health Center in the work area of the Banjar City Health Office is very high. With the highest value on the quantity indicator produced and the lowest value on the reaction indicator. Workload and training education have a positive effect on the performance of immunization officers at the Health Center in the work area of the Banjar City Health Office. This means that if the workload and training education are increased, the performance of immunization officers at the Health Center in the work area of the Banjar City Health Office will also increase.